Correlação entre o uso de batom e a concentração de parabenos em mulheres expostas ao cosmético - Tahan, Gabriella Padovani (2015)
Parabens preservatives are widely used in the cosmetic, pharmaceuticals and food industry as additives. They have a long history of use since they are economically very advantageous and it is thought that they are relatively nontoxic to humans. However, recent studies indicate that parabens may have estrogenic activity. Lipstick is a cosmetic widely used by women and the components of it can be absorbed by both the oral mucosa, as the digestive tract. The Cosmetotoxicology is a new specialty within the Toxicology, which came about thanks to the demands of the productive and the regulatory sector, and aims to obtain and release of safe and standardized products to the public. In this context, there is a growing demand for the development of analytical methods to quantify parabens in cosmetics with reliably for inspection and quality control. Furthermore, since the kinetic data of these substances are not known, is also necessary to develop methods to quantify these analytes in biological matrices. Thus this paper proposes, for the first time a correlation between the use of lipstick and the amount of parabens in women who make use of this cosmetic. Methodologies of parabens analysis both in lipstick and in blood were developed and validated following validation protocols and the results were satisfactory for all parameters such as selectivity, detectability, linearity, precision and accuracy. Samples of 18 volunteers were analyzed in three stages, which in one of these stages, they made use of lipstick with parabens in a known concentration. After statistical processing of data, using a non-parametric tests, it was concluded that there is absorption of parabens through the use of lipstick, as was demonstrated statistically significant difference (p <0.05, the Friedman test) between the concentrations of parabens in the serum of women who used lipstick containing these substances, in relation to the non-use of cosmetic lip and was demonstrated strong correlation (Spearman coefficient r = 0.7205) between the used amount of lipstick and the concentration of parabens in serum.